PENGARUH IKLIM ORGANISASI, SALARY, DAN STRES KERJA TERHADAP JOB SATISFACTION (Studi pada karwayan Metor Cell Kota Malang) - Havisfal Alviansyah; Abd kodir Djaelani; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThe purpose of this study is to determine and analyze the influence of Organizational Climate Salary, and Job Stress on Job Satisfaction of Malang City Meteor Cell employees. The sample used was all employees of the Central Malang Meteor Cell. The Sampling Technique which if it is less than 100 is better taken all then this study is a census study. Based on the results of the study note that the independent variables simultaneously have a significant effect on the dependent variable, the value is known with a sig value below 0.05, then H1 is accepted, meaning that the Organizational Climate and Work Stress variables simultaneously influence the Job Satisfaction. Like the Organizational Climate variable, which is known with a sig value below 0.05, it means that the Organization Climate has a partial effect on Job Satisfaction. Salary variable is known with a sig value below 0.05, meaning that the Salary variable has a partial effect on Job Satisfaction. While the Work Stress Variable is known by the value of sig. above 0.05, it means that the Job Stress variable has no significant effect on Job Satisfaction.Keywords: Orgaizational Climate, Salary, Job Stress, Job Satisfaction.